SYNTHESIS AND CHARACTERISATION OF ANTIGENIC MELANOMA CANCER PEPTIDES FOR ANTI-CANCER DRUG DESIGN - Kizilbey, Kadriye; Ozdemir, Zafer Omer; Mustafaeva, Zeynep (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2012)
Malignant melanoma is the most dangerous form of skin cancer and commonly diagnosed cancer with an increasing incidence. Melanoma is a curable in the case of thin tumours, however, if the tumour becomes thick and deep, then the disease is difficult to control and will often spread to the other parts of the body. The objective was the synthesis and characterisation of NY-ESO-1 155-163 (Q-L-S-L-L-M-W-I-T) and MAGE-3 121-134 (L-L-K-Y-R-A-R-E-P-V-T-K-A-E) antigenic peptide sequences of melanoma tumour cancer by microwave enhanced solid phase peptide (SPPS) synthesis method. The peptides were characterised by liquid chromatography-electrospray interface-mass spectrometry (LC-ESI-MS) with electro spray ionisation. The reason for these two synthetic peptides election is due to their potential as an anti-cancer drug design, therapeutic agent or synthetic vaccine for Melanoma disease.
Keywords: MAGE-3; melanoma; microwave; NY-ESO-1; peptide vaccine; Solid Phase Peptide Synthesis (SPPS); tumour cancer; VACCINE; IDENTIFICATION; EPITOPES; SYSTEM; TESTIS; Environmental Sciences & Ecology